2019
DOI: 10.1002/lary.27815
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery for Type‐2 CRS wNP: An Endotype‐Based Retrospective Study

Abstract: Objectives Nasal polyps are often characterized by type 2 inflammation and disease recurrence. We developed a new surgical technique, referred to as reboot approach, which aims to maximally remove all sinus mucosa and allow healthy re‐epithelialization from the preserved nasal mucosa. We here review type 2 endotype chronic rhinosinusitis with nasal polyps (CRSwNP) patients who underwent classical mucosa‐sparing endoscopic sinus surgery (ESS) or the reboot approach. Methods Retrospective case‐control study of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 35 publications
7
98
0
2
Order By: Relevance
“…Some studies have reported greater/faster symptoms reduction and less disease recurrence following surgeries compared with appropriate pharmaceutical managements alone in certain subgroups of chronic rhinosinusitis (Fokkens et al, 2019;Alsharif et al, 2019;Wang, Gullung & Schlosser, 2011). However, the appropriateness of primary EPLAs to treat lesions due to inflammation in rhinosinusitis has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported greater/faster symptoms reduction and less disease recurrence following surgeries compared with appropriate pharmaceutical managements alone in certain subgroups of chronic rhinosinusitis (Fokkens et al, 2019;Alsharif et al, 2019;Wang, Gullung & Schlosser, 2011). However, the appropriateness of primary EPLAs to treat lesions due to inflammation in rhinosinusitis has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…If necessary, this procedure is combined with a Draf type-III procedure. Reboot surgery shows significantly lower rates for polyp recurrence as well as a longer recurrence-free time and lower values in the SNOT-22 compared to conventional FESS [111].…”
Section: American Academy Of Otolaryngology-head and Neck Surgerymentioning
confidence: 90%
“…The extent of sinus surgery is usually adapted to the type and extent of disease as well as the individual anatomy. Surgical techniques range from polypectomy alone to partial uncinectomy, FESS and more extended surgical approaches like "nasalization", "reboot surgery" or "full-house FESS with Draf III" [110][111][112][113]. Individual terms such as MIST (minimally invasive sinus technique) are part of the spectrum of possible extents of surgery.…”
Section: Extent Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…24 To completely remove not only the sinus mucosa, including the polyps, but also the thickened and equally diseased mucosa next to them (Jonstam et al 2020, submitted for publication) prepared to develop polyps also, which may be a valid approach to a severe case of type 2 mucosal disease involving all the sinuses. 25 This approach, which has been termed reboot, may also involve the frontal sinuses and builds on the observation that the new mucosa growing into the sinuses from the nasal cavity shows less polyp formation. Nasal mucosa may also show type 2 bias, but it very rarely forms polyps, and thus overgrows the sinuses as a thin but functional mucosa within a few weeks after surgery.…”
Section: Phenotypes Versus Endotypes: Decisive For Treatment Optimizamentioning
confidence: 99%